Juiz de Fora/MG more resilient: Civil Defense in Schools Project in favor of sustainable development - Santos, Aline Gasparoni dos; Toledo, Ana Carolina Marini Magalhães de; Costa, Camila Rosa Galvão da; Assis, Joviano Elias de Souza; Martins, Luís Fernando (Technical and Scientific Journal Green Cities, 2025)
Faced with the disorderly growth of cities, there is an increase in dangerous situations and vulnerabilities, which results in the formation of risk areas. This problem, combined with climate change that has been occurring around the world, has favored the occurrence of disasters, negatively affecting human daily life. The Hyogo Framework, the Sendai Action Framework and the National Civil Protection and Defense Policy (PNPDEC) highlight the importance of environmental education and resilience to reduce disaster risks. Therefore, in order to minimize the impacts of adverse events and the consequent social, environmental and economic losses, investment in pre-disaster actions becomes essential. Therefore, based on a bibliographical review and case study, this article sought to list the main educational actions promoted by the Civil Defense of Juiz de Fora/MG, which aim to increase risk perception and disseminate the importance of environmental sustainability, through of interactive and playful methodologies, detailing the methods used, in addition to providing examples that show how it is possible to work on Civil Defense themes in classrooms. With all of the above, it is expected to contribute to the improvement of municipal management and disaster risk management, in addition to disseminating the actions that obtained positive results to other Civil Defenses and educational institutions.
Keywords: Disaster Risk Management; Preventive actions; Environmental education